A novel measurement of marginal Alfvén eigenmode stability during high power auxiliary heating in JET. (1st July 2022) - Tinguely, R.A.; Fil, N.; Puglia, P.G.; Dowson, S.; Porkolab, M.; Guillemot, V.; Podestà, M.; Baruzzo, M.; Dumont, R.; Fasoli, A.; Fitzgerald, M.; Kazakov, Ye.O.; et al.
Abstract: The interaction of Alfvén eigenmodes (AEs) and energetic particles is one of many important factors determining the success of future tokamaks. In JET, eight in-vessel antennas were installed to actively probe stable AEs with frequencies ranging 25–250 kHz and toroidal mode numbers | n | < 20. During the 2019–2020 deuterium campaign, almost 7500 resonances and their frequencies f 0, net damping rates γ < 0, and toroidal mode numbers were measured in almost 800 plasma discharges. From a statistical analysis of this database, continuum and radiative damping are inferred to increase with edge safety factor, edge magnetic shear, and when including non-ideal effects. Both stable AE observations and their associated damping rates are found to decrease with | n |. Active antenna excitation is also found to be ineffective in H-mode as opposed to L-mode; this is likely due to the increased edge density gradient's effect on accessibility and ELM-related noise's impact on mode identification. A novel measurement is reported of a marginally stable, edge-localized ellipticity-induced AE probed by the antennas during high-power auxiliary heating (ion cyclotron resonance heating and neutral beam injection) up to 25 MW. NOVA-K kinetic-MHD simulations show good agreement with experimental measurements of f 0, γ, and n, indicating the dominance of continuum and electron Landau damping in this case. Similar experimental and computational studies are planned for the recent hydrogen and ongoing tritium campaigns, in preparation for the upcoming DT campaign.